Importance of Public Interests in Patent Law - O. V. Pikhurets; A. O. Pikhurets (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on studying and explaining the legal nature and content of public interests from point of view оf the patent protection system in the context of globalization processes. The problems of the influence of patent rights on the possibility of individuals to realize their rights in the health care sector are identified. The concepts of private and public interests, their ratio, content featurs in patent law are analyzed. The defining value of interest is fixed at the normative level in civil law, where intellectual property law is its sub-branch. In general, private interest can be both property and non-property. In this context, the provisions of national and international legislation of the necessity оf balance the interests of society and patent holders are analyzed; on restricting the rights of patent owners with the aim to ensure the public interest; about necessity in certain cases to break the monopoly of patent owners through compulsory licensing, etc. The tendency to strengthen the protection of public interests has been revealed. Attention is paid to the issue of distinguishing between the private interests of patent holders and the interests of society. It is clarified why these interests collide and what rules justify such conflicts. The conclusion that necessity to ensure a balance between private and public interests is substantiated as the urgent task of modern legislation in the legal regulation of patent relations.